Madrasah Transformation Into Modern Educational Institutions During The New Order - Basri Ibrahim (ISTAWA, 2019)
Madrasah is an Islamic educational institution growing rapidly and significantly in Indonesia to become one of the modern educational institutions. Madrasah in the early period of growth and development is a single educational institution for the community which aims to explore the basics of Islam. However, with advances in the thinking of Islamic scholars, the madrasah undergoes a transformation both of institutional and educational system, the change is very significant madrasa occurred in the new order. The conversion was evident in three (3) ways, namely (a) the system overhauls madrasa changed to be a gap system and classical; (B) a blend of everyday materials and curriculum between religious elements; and (c) the variety of institutional models madrasah with unique features and characteristics. As a result of this transformation is made while positioning the madrassa parallel with other educational institutions in Indonesia. Thus the madrasa has a strategic role for improving the quality of Islamic education, which has its colour of other educational institutions in Indonesia.Madrasah adalah lembaga pendidikan Islam yang berkembang pesat dan signifikan di Indonesia menjadi salah satu lembaga pendidikan modern. Madrasah pada periode awal pertumbuhan dan perkembangan adalah lembaga pendidikan tunggal bagi masyarakat yang bertujuan untuk mengeksplorasi dasar-dasar Islam. Namun, dengan kemajuan pemikiran para cendekiawan Islam, madrasah mengalami transformasi baik dari sistem kelembagaan maupun pendidikan, perubahan madrasah sangat signifikan terjadi pada masa orde baru. Konversi tersebut terbukti dalam tiga (3) cara, yaitu (a) sistem perbaikan madrasah berubah menjadi sistem kesenjangan dan klasik; (B) perpaduan bahan sehari-hari dan kurikulum antara unsur-unsur agama; dan (c) ragam model kelembagaan madrasah dengan fitur dan karakteristik unik. Sebagai hasil dari transformasi ini dibuat sambil memposisikan madrasah sejajar dengan lembaga pendidikan lainnya di Indonesia. Dengan demikian madrasah memiliki peran strategis untuk meningkatkan kualitas pendidikan Islam, yang memiliki warna lembaga pendidikan lain di Indonesia.